Pemodelan Kasus DBD di Provinsi Jawa Timur dengan Metode Data Panel - Annisa Dwinda Shafira (Universitas Airlangga, 2019)
The combination of panel data regression consist of time series data, it was collected based on a characteristic at a certain time (cross section). This research aimed to analyze the affecting factors and dominant factors of Dengue Hemoragic Fever (DHF) cases in East Java using panel data regression. This research uses secondary data published by the East Java Provincial Health Office, namely the Health Profile and the East Java Provincial Statistics Agency such as documents of each Districts/City in Numbers of East Java on 2014–2017 using total research population that were collected in all districts/cities in East Java Province. The data of new cases of DHF and factors affecting the incidence of DHF including clean and healthy living behavior in the household, poverty, population density, rainfall in East Java on 2014–2017. Panel regression analysis is used to determine the best model of the CEM, FEM and REM using Chow test, Hausman test and Langrange Multiplier test. Based on the results, the best model of panel regression is FEM with affecting variables such as poverty, population density, and rainfall.